Impact of Perceived Social Responsibility on Consumers' Green Perception and Green Behavior: The Moderating Role of Personality Traits - Ghasem Zarei; Khadijeh Mirzaei (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2022)
Green behavior plays an essential role in the continuation of human life. This study aimed to investigate the effect of perceived social responsibility on green perception and behavior. The study was conducted using quantitative methods, sampling a questionnaire to 450 customers of various one-chain store branches in Iran through convenience sampling. The study was conducted from 16 May 2018 through 20 June 2018. Data from the moderating bootstrap analysis was used in PROCESS to analyze the data. The results indicated significant, positive correlations between social responsibility, on the one hand, and green perception and consumers' green behavior, on the other hand. In terms of strength, the coefficients indicated moderate relationships (r=0.345 and r=0.288, respectively). Indirect effects were studied using Macro bootstrap. It was revealed that green perception (β=0.0652) predicts consumers' green behavior and is a moderating variable. Additionally, the moderating impacts of extroversion and openness in the relationship between consumers' green perception and green behavior were identified. According to the research, in addition to increasing social responsibility, companies should try to increase customers' perception of this behavior to help green consumption.